BENEFITS OF SQUARES IN URBAN AFFORESTATION - THE CASE OF CUIABÁ/MT - Oliveira, Angela Santana; Sanches, Luciana; Musis, Carlo Ralph de; Nogueira, Marta Crista de Jesus Albuquerque (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707695 The urban forestry contributes directly to the quality of life in cities, benefiting theirphysical-environmental. Examining the case of two public squares in Cuiabá, Brazil, this studyinvestigated how trees affect the conditions of the microclimate in urban areas. This study aimedto assess the variables that contribute the thermal environment of squares Popular and April 8and how this influences the use by people analyzing the relationships among the factors involvedin this process, mainly through the woody vegetation. This involved measurements of leaf areaindex (LAI), rates of shading and tree density (ISA and IDA), size and identification of variousspecies. Also, we performed measurements of meteorological variables for 15 continuous days ona rainy dry season and another in 2009. Held parallel to one behavioral assessment verification ofthe dynamics of use by people. It was observed that the mean air temperature below the canopywas reduced by 0.45 ° C and 0.30 ° C respectively in dry and rainy seasons. By multivariate analysisusing clusters of vegetation characteristics, the results indicated dichotomy resulting in a numberof areas with high leaf area index and large trees, and another group with less leaf area index, treesize and percentage of shaded area. It was concluded that it is important to add efforts to qualifythe environment through public squares better planning and proper methodology in selecting treespecies to be adopted.